The sources of competitive advantage from the perspective of project management - results of empirical studies = Źródła przewagi konkurencyjnej z perspektywy zarządzania projektami - wyniki badań empirycznych - Dolata, Magdalena (Zielona Góra: Faculty of Economics and Management Press)
The aim of the paper is entering the discussion concerning the sources of competitive advantage in project management in basic local government units in Poland. The focus of the paper is placed on the selected elements of the sources of competitive advantage in basic local government units in Poland, namely tasks implemented in projects. The paper consists of two main parts.
Keywords: dojrzałość projektowa; zarządzanie projektami; doskonałość w zarządzaniu projektami; przewaga konkurencyjna; project maturity; project management; excellence in project management; competitive advantage